Simultaneous reduction of radiation dose and scatter for CBCT by using collimators. Issue 12 (26th November 2013) - Li, Tianfang; Li, Xiang; Yang, Yong; Zhang, Yongqian; Heron, Dwight E.; Huq, M. Saiful
Abstract : Purpose: : On‐board cone‐beam CT (CBCT) imaging has been widely available in radiotherapy clinic for target localization. However, the extra radiation dose from CBCT is always a concern for its frequent use. Additionally, the relatively large scatter in CBCT often degrades the image quality. By using collimators, some of the X‐rays can be stopped from reaching the patient and the detectors, hence both the scatter and the patient doses are simultaneously reduced. The authors show in this work that the collimated CBCT data can be reconstructed without any noticeable artifacts for certain collimator blocking ratios and blocking patterns, and the focus of this work is to study the relationship between the image quality and these two collimator factors. Methods: : A CBCT system with collimators was simulated following the typical geometry used in clinic. Different collimator designs were tested by varying the size and the number of the collimator slits, and at the same time, the ratio of transmitted beams to total beams was varied from 100% to 10%, resulting in hundreds of different simulation scenarios. Lung and pelvis phantoms created from patients CT images were used in the simulations, and an iterative reconstruction algorithm using the compressed sensing technique was adopted. The image quality was examined by root mean square errors (RMSEs) and compared with the conventional CBCT images. Results: : The CBCT image quality increases as the amount of beams passing through the collimators increases, and decreases as the size of the collimator slits increases. With ultra‐high resolution collimators, the RMSEs were comparable to the conventional CBCT image quality until the beam transmission rate is reduced below 25%. Conclusions: : Collimators can reduce the scatters and radiation dose, however, the collimated CBCT image quality is strongly dependent on both the collimator blocking ratio and the blocking pattern. To achieve image quality comparable to the conventional CBCT, the amount of information and data format must be adequate.